(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
The integration of Artificial Intelligence (AI) technologies into language education has transformed English as a Foreign Language (EFL) instruction worldwide. Among these technologies, ChatGPT has gained significant attention due to its ability to provide immediate feedback, language support, and writing assistance. This study investigates the impact of ChatGPT-assisted writing on EFL students’ academic writing performance. The paper explores theoretical foundations, empirical evidence, practical applications, and instructional strategies related to AI-assisted writing. The findings suggest that ChatGPT can improve grammatical accuracy, lexical diversity, coherence, and organization when used appropriately. However, excessive dependence on AI may hinder learners’ creativity and autonomous writing development. The study concludes that ChatGPT should be used as a writing support tool rather than a replacement for students’ independent writing efforts.